Anticholinesterase and Antioxidant Activities of Natural Abietane Diterpenoids with Molecular Docking Studies - Topçu, Gülaçtı; Akdemir, Atilla; Kolak, Ufuk; Öztürk, Mehmet; Boğa, Mehmet; Bahadori, Fatemeh; Çakmar, Seda Damla Hatipoğlu (Current Alzheimer Research, 2020)
Background: Alzheimer’s Disease (AD) is one of the most prevalent causes of dementia in the world, and no drugs available that can provide a complete cure. Cholinergic neurons of the cerebral cortex of AD patients are lost due to increased activity of cholinesterase enzymes. Objective: Acetylcholinesterase (AChE) and Butyrylcholinesterase (BuChE) are the two major classes of cholinesterases in the mammalian brain. The involvement of oxidative stress in the progression of AD is known. Thus, the objective of this study is to determine strong ChE inhibitors with anti-oxidant activity. Methods: In this study, 41 abietane diterpenoids have been assayed for antioxidant and anticholinesterase (both for AChE and BuChE) properties in vitro, which were previously isolated from Salvia species, and structurally determined by spectroscopic methods, particularly intensive 1D- and 2DNMR and mass experiments. Molecular modeling studies were performed to rationalize the in vitro ChE inhibitory activity of several abietane diterpenoids compared with galantamine. Results: Thirteen out of the tested 41 abietane diterpenoids exhibited at least 50% inhibition on either AChE or BuChE. The strongest inhibitory activity was obtained for Bractealine against BuChE (3.43 μM) and AChE (33.21 μM) while the most selective ligand was found to be Hypargenin E against BuChE enzyme (6.93 μM). A full correlation was not found between anticholinesterase and antioxidant activities. The results obtained from molecular modelling studies of Hypargenin E and Bractealine on AChE and BuChE were found to be in accordance with the in vitro anti-cholinesterase activity tests. Conclusion: Abietane diterpenoids are promising molecules for the treatment of mild-moderate AD.
Keywords: abietane diterpenoids